View invariant description of curved objects using higher degree implicit polynomials - Satish Kaveti. (2008)
In this thesis, we have studied the problem of obtaining view invariant description of curved 3-D objects and free-form planar objects using implicit polynomials. The emphasis of our work is on development of an efficient algorithm for obtaining invariants.